Dimensi Akuntabilitas Kinerja Instansi Pemerintah Daerah - Dri Asmawanti; Aisyah Mayang Sari; Vika Fitranita; Indah Oktari Wijayanti (Journal of Applied Accounting and Taxation, 2020)
This study aims to test the influence of the implementation of the system of internal control of government and compliance with laws and regulations on the performance accountability of government agencies. The data is using the primary data obtained from the results of the distribution of questionnaires to the head of the Regional Device Organization in the office of government agencies of Bengkulu City. The result of hypothesis testing shows that the application of the government's internal control system and the obedience to the regulation have a positive effect on the performance accountability of government agencies. From the results of this study, shows that the performance accountability of government agencies are required to improve the implementation of government internal control system and compliance with laws and regulations that will improve the accountability of performance control system of government agencies of Bengkulu City.